Experience Marketing Influence on Customer Loyality in Dapur Iga Restaurants - Nazhif, Muhammad Wildan; Dhewanto, Wawan (Journal of Business and Management, 2013)
Dapur Iga is one of restaurant which locate in Bandung, today it going to become franchise business. Dapur Iga restaurant provide some variety food specialty grilled ribs with many kind of sauce. Dapur Iga locate in Jl.Veteran No.42 with western concept. Sales per day are decrease so that the writer want to make a research in this restaurant. The writer objectives to see is there any influence of experience marketing on customer loyalty in Dapur Iga restaurant and how much the influence if they have. Experience marketing is one tool of marketing which make the customer who has bought the product or service which touching their heart so that their remind it and make them tell their nearest people. Customer loyalty is a result that customer satisfied with the product that they bought which make them buy again or recommend to others. Customer satisfaction is added variable because customer satisfaction has relation with customer loyalty. Data collection in this study is using a questionnaire distributed to Dapur Iga consumers as the population with 200 samples. Writer use Microsoft Excel, SPSS 17.00, and SPSS 20.00 to process the data and analysis with PathÂ  Analysis. After process the data, researcher gets conclusion that experience marketing has significantly effect to customer loyalty in Dapur Iga with individually affects 42.8% and simultaneously 56%. Dapur Iga need to improve their interaction with customer because that factor is dominant to influence in this case.Â Key-Words: Experience Marketing, Customer Satisfaction & Customer Loyalty